Investigação Dopplercardiográfica da valvopatia reumática subclínica - Fernanda Aparecida de Oliveira P. Guimaraes (2003)
Objective: To characterize the clinical and Doppler echocardiography of valvular lesions in rheumatic fever, the acute to the chronic stage of disease, determining the prevalence of subclinical chronic valvopathy.Methods: Cohort of 57 patients with rheumatic fever followed up at Hospital das Clinicas, Federal University of Goiás, between November, 1989 and November, 2002, which were evaluated in two phases: a first phase, the first acute outbreak, analyzing the features of clinical disease and tests for assessment of cardiac involvement: chest radiography, electrocardiography and Doppler echocardiography. In the second phase four surgical patients were excluded, ending the study with 53 participants, in which the same acute phase variables have beenreassessed, with emphasis on cardiac auscultation, analyzing the evolution of cardiac disease, from acute to chronic phase. Data were analyzed by Analysis and Statcalc programs through the EPI INFO 6.04, and calculated sensitivity, specificity, positive and negative predictive values of clinical examination in the diagnosis of subclinical chronic valvopathy, and comparative analysis of the valve lesion in the chronic phase, between cardiac auscultation, complemented by chest radiography and eletrocardiography, and Doppler echocardiography, considering the range of 95%. Results: The results of evolutionary analysis, through Doppler echocardiography, showed that 24.5% of the acute phase valvular lesions regressed for healing in the chronic phase, which the majority of these acute lesions (83.3%) were mild. No serious injury devolved to cure, yet each has regressed to moderate condition. Still in the analysis of the results of Doppler echocardiography, were found in this study 34 (64.1%) patients with chronic valvular disease with mitral valve lesions present in almost all tests. When compared with auscultation, 10 patients were identified with cardiac auscultation, chest radiography and electrocardiographic normal, but with valvular lesions. The sensitivity of cardiac auscultation to valvular lesions proved to becompromised, leading to false-negative examinations, which were called subclinical chronic rheumatic valvopathy. Conclusions: After analyzing the results of this research, it is proposed that Doppler echocardiography be performed following all patients in the chronic phase of the rheumatic fever, regardless of the presence of normal results on cardiac examination, chest X-ray and electrocardiogram